Eriodictyol Attenuates Myocardial Ischemia-Reperfusion Injury through the Activation of JAK2 - Defang Li; Ning Lu; Jichun Han; Xiaoyu Chen; Wenjin Hao; Wenjuan Xu; Xiaona Liu; Lei Ye; Qiusheng Zheng; Qiusheng Zheng (Frontiers Media S.A., 2018)
Myocardial ischemia-reperfusion (I/R) injury remains the leading risk factor of disability and mortality worldwide. In this study, the myocardial protective effect of eriodictyol (EDT) and the underlying mechanism in an ex vivo model of global myocardial I/R was investigated. After treatment with different concentrations of EDT, the decreased hemodynamic parameters induced by myocardial I/R injury were significantly attenuated by EDT. The elevated levels of IL-6, CRP, IL-8, and TNF-α were effectively reduced by EDT treatment. EDT also remarkably suppressed the levels of Bax and cleaved Caspase-3, and up-regulated the level of Bcl-2 in cardiac tissues from EDT-treated groups. Further studies showed that EDT could increase the levels of p-JAK2 and p-STAT3 in cardiac tissues. Meanwhile, treatment of AG490, a specific inhibitor of JAK2, abolished the protective effect of EDT on hemodynamic parameters, myocardial inflammation and myocardial cell apoptosis induced by I/R injury. These results demonstrated that EDT could protect against myocardial I/R injury through the activation of JAK2, providing a potential treatment with EDT during myocardial I/R injury.